Glass Ceiling in Focus: A Comprehensive Bibliometric Review of Business and Management Studies - Mahat, Dipak (Darul Yasin Al Sys, 2024)
The glass ceiling continues to impede women's progression into leadership roles within Business and Management Studies. Despite increased awareness of gender inequality, systemic challenges remain pervasive. This study aims to conduct a bibliometric review to elucidate the trends, key contributors, and geographical landscape related to the glass ceiling from 1999 to 2024. A systematic review methodology was employed, sourcing data from the Scopus database using the keyword